PEMBERDAYAAN DAN PENINGKATAN PENGETAHUAN KADER TENTANG PENGOLAHAN MAKANAN LOKAL UNTUK MENINGKATKAN STATUS GIZI BALITA DI KELURAHAN CIAPADUNG KIDUL- KOTA BANDUNG - Yosef Pandai Lolan; Tuti Suprapti; Roganda Situmorang; Nisa Indah Pertiwi; Rikky Gita Hilmawan (Edukasi Masyarakat Sehat Sejahtera (EMaSS) : Jurnal Pengabdian kepada Masyarakat, 2023)
Based on BPB activities, there were 9,657B recorded. children under five (8.93%) with stunting status (chronic nutritional problems) out of 107,189 children under five weighed in the city of Bandung in 2020. From this data, 2.27%, or 2,434 children under five are very short and 6.65%, or 7,133 Toddlers with short status. The percentage of stunting under five in 2020 is close to the highest percentage of stunting under five in 2015 at 8.96%. During this period, the highest percentage of stunting under five was in 2015 (8.96%), and the lowest was in 2017 (1.94%) (Bandung City Health Office 2020). Looking at the relatively large population data in the city of Bandung, we are trying to carry out community service activities that take the theme of local food processing, where this empowerment activity focuses on local food processing to cadres and provides knowledge about parenting patterns for providing nutritious food. The stages of implementing this activity include identifying community needs. Before carrying out community service activities, first, identify community needs and observe various problems faced by the residents of the Cipadung Kidul Village, the working area of ​​the Panyileukan Health Center in the vicinity, then draw a theme based on these problems. In this activity, we are trying to make 2 types of local food: Tempe Sandwich and Tempe Kastu. Of course, these two types of food are prepared with ingredients that are safe and easy to find. As for some combinations of food, such as tempeh, eggs, white bread, etc. (can be seen in the following image)